Bias Effects on Total Dose-Induced Degradation of Bipolar Linear Microcircuits for Switched Dose-Rate Irradiation - Velo, Y Gonzalez; Boch, Jérôme; Roche, Nicolas Jean-Henri; Perez, Stephanie; Vaille, Jean-Roch; Dusseau, Laurent; Saigne, Frédéric; Lorfevre, Eric; Schrimpf, Ronald D; Chatry, Christian; Canals, Anna (IEEE transactions on nuclear science, 2010)
Accelerated test techniques are needed in order to qualify bipolar devices intended for use in low dose rate environments. Indeed, low dose rate is known to enhance degradation of bipolar devices. Moreover, the bias of microcircuits is known to play a significant role in device degradation. In this work, bipolar microcircuits are irradiated with different bias configurations during the irradiation. It is shown that the bias configuration leading to the worst-case degradation is dose-rate dependent. Moreover, if a time-saving evaluation technique based on dose-rate switching is to be used, the effect of bias has to be investigated. In this work, this time-saving technique, the switched dose-rate technique, is applied for the first time to evaluate the behavior of dynamics parameters of a bipolar IC irradiated all pins grounded, and also to evaluate the behavior of static and dynamics parameters of bipolar ICs irradiated under several bias configurations. Good agreement is found between the predictive curve obtained with the switched dose-rate technique and the low dose rate data.